2018
DOI: 10.2147/cmar.s181178
|View full text |Cite
|
Sign up to set email alerts
|

The association between metabolic syndrome and bladder cancer susceptibility and prognosis: an updated comprehensive evidence synthesis of 95 observational studies involving 97,795,299 subjects

Abstract: BackgroundThe association between metabolic syndrome (MS) and bladder cancer (BC) was not fully investigated, and most primary studies and pooled analyses were only focused on certain specific components.ObjectiveTo further investigate this issue and obtain more precise findings, we conducted this updated evidence synthesis of published studies, which involved not only MS components but also the MS in its entirety.Materials and methodsWe searched the PubMed, EMBASE, and Web of Science databases for observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 118 publications
3
17
0
Order By: Relevance
“…Beyond smoking, other risk factors for BCa have been studied, including metabolic syndrome (MS), obesity, and type 2 diabetes mellitus (T2DM) [ 3 , 4 , 5 ]. Based on large cohorts, T2DM significantly increased the risk of BCa [ 6 , 7 ], but findings from a meta-analysis suggest that individuals with T2DM may have a modestly increased risk of BCa [ 8 ] or none according to a population-based case-control study [ 9 ]. Still, analysing a vast population, data do not support an association of T2DM with overall bladder cancer incidence from 1992 through 2007 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond smoking, other risk factors for BCa have been studied, including metabolic syndrome (MS), obesity, and type 2 diabetes mellitus (T2DM) [ 3 , 4 , 5 ]. Based on large cohorts, T2DM significantly increased the risk of BCa [ 6 , 7 ], but findings from a meta-analysis suggest that individuals with T2DM may have a modestly increased risk of BCa [ 8 ] or none according to a population-based case-control study [ 9 ]. Still, analysing a vast population, data do not support an association of T2DM with overall bladder cancer incidence from 1992 through 2007 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The recent publication has reported the similar result (HR: 1.03, 95% CI: 1.01-1.05) (22). In 2018, Peng et al (23) have performed an updated meta-analysis to examine the relationship between metabolic syndrome and susceptibility and prognosis of bladder cancer. The pooled results indicated that diabetes history significantly increased the risk of bladder cancer and was associated with poor survival.…”
Section: Discussionmentioning
confidence: 79%
“…Well-established risk factors for bladder cancer include tobacco smoking and exposure to certain chemicals in the working and general environments (3). Emerging evidence has shown that metabolic syndrome, obesity, low physical activity, and type 2 diabetes are related to an increased risk of bladder cancer (4)(5)(6)(7)(8), suggesting that insulin resistance may play a role in the etiology of bladder cancer.…”
Section: Introductionmentioning
confidence: 99%